Illocutionary Act Analysis on United Nations Women Press: Gender Equality in the 2030 Agenda - Fadzila, Nadia Nur (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2023)
Illocutionary acts as part of the study of Pragmatics concern with the speakers’ intended meaning when they make utterances. The intended meaning can be the same as the literal meaning in the locution or it has different meaning depending on the context of the utterances. This paper reports on the illocutionary acts in the text of “Gender Equality in the 2030 Agenda” that is released in a press conference held by United Nations Women on February 15, 2018. Using categorization of type of Illocutionary acts from Yule (1996), that are representative, directive, commissive, expressive, and declarative. This study asked the question of what kind of illocutionary acts are found in the text and what is the dominant of them. The data was collected through documentation from UN women’s press website. This study found 5 types of illocutionary acts with a total of 44 data. The results of the study showed 27 representative illocutionary acts consisting of 1 warning, 7 assumptions, 10 demands, 6 affirmations, 1 stating, and 2 hypotheses, while commissive was found in total of 8 data, consisting of 3 promises, 1 swears, 3 advises, and 1 does. Directives type of illocution was found only in 2 utterances; both are about advice. Expressive Illocution was found in 3 data, comprising 1 praise, 2 thank. Lastly, directive was found in 4 utterances with 3 states and 1 asks. Therefore, the most widely used illocutionary speech act is representative with 27 utterances.